Gaining a foothold in the world “for a better life”. Encounters between inhabitants and tourists in Lalibela (Ethiopia), a small World Heritage town - Marie Bridonneau (Via@, 2014)
This article presents some reflections on encounters between international tourists and local society, based on fieldwork carried out between 2009 and 2011 in Lalibela, a small heritage and tourist town in northern Ethiopia. Beyond the “criticist paradigm” which highlights the harmful effects of tourism in certain social spaces of the South, it aims at showing how the encounter with tourists is a moment of connecting with the World for a local society which otherwise has very few contacts with international flows, or a moment of hybridisation of cultural practices and representations. We will also consider the social and economic dynamics of these relations, which are not built on fortuitous encounters but result from strategies involving certain groups, usually of young men, who seek out the relationship and then make it last. In this context, the emblematic stories of a few fortunate “sponsored” people fuel the fantasies of young people seeking to gain a foothold in the world and a “better life”.